PREVALENCE OF TOXOPLASMA GONDII IGG AND IGM AND ASSOCIATED RISK FACTORS AMONG HIV-POSITIVE AND HIV-NEGATIVE PATIENTS IN VHEMBE DISTRICT OF SOUTH AFRICA - Ngobeni, Renay; Samie, Amidou (African Journal of Infectious Diseases (AJID), 2017)
Background: Toxoplasma gondii is a zoonotic parasite that has arisen as an important opportunistic infection that causes morbidity and mortality especially in HIV positive patients. This study was carried out to determine the sero-prevalence of T. gondii (IgG and IgM) and the associated risk factors among HIV positive and negative patients in Northern South Africa. Materials and Methods: The study was conducted in the Vhembe District in Limpopo province from April 2012 to January 2013. A well-structured questionnaire was used to collect socio-demographic information and possible risk factor information on toxoplasmosis from participants. A total of 161 blood samples of both HIV positive and negative patients visiting the local clinics in the Vhembe district were collected. Serum samples were tested for IgG and IgM against T. gondii using commercially available ELISA protocol. Results: The prevalence of T. gondii IgG was 31.7% while that of T. gondii IgM was 4.9%. The prevalence of T. gondii IgG was higher in HIV positive patients (38%) compared to 16.7% among HIV negative patients (p=0.001). Toxoplasma gondii IgG antibodies were more common in patients who were not taking ARV’s (46.2%) compared to those who were taking ARV’s (35.2%) (P<0.001). Conclusions: The present study has shown a high prevalence of T. gondii (IgG) among patients attending different HIV clinics in the Vhembe district with no current infections among pregnant women. In addition to the sero-positive status of the patient to HIV, other significant risk factors for toxoplasmosis included high viral load, non-adherence to ARV therapy and age (>25 years).